EMPLOYMENT OPPORTUNITIES AND CHALLENGES FOR PEOPLE WITH INTELLECTUAL DISABILITIES: A GLOBAL PERSPECTIVE - Naresh Kumar Jaiswal (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2024)
This paper explores the employment landscape for people with intellectual disabilities (ID), providing a comprehensive global perspective on both the opportunities and challenges they face. Employment is a critical aspect of social inclusion and economic independence, yet individuals with ID often encounter significant barriers. This study reviews these barriers, such as societal attitudes, limited access to education and vocational training, and insufficient workplace accommodations. It also examines the effectiveness of international and national policies aimed at promoting inclusive employment. Through a mixed-methods approach, the paper identifies successful employment models and programs from various regions, including supported employment and corporate social responsibility initiatives. By highlighting best practices and offering recommendations, this paper aims to inform policymakers, employers, and advocates on how to enhance employment outcomes for people with ID, ultimately fostering more inclusive and diverse workplaces and societies.